2010
DOI: 10.1111/j.1540-8167.2010.01964.x
|View full text |Cite
|
Sign up to set email alerts
|

Tachycardia Transition During Ablation of Persistent Atrial Fibrillation

Abstract: Transition to a second AT occurs frequently in the midst of ablation of AT in persistent AF patients. This transition occurs most commonly abruptly within the range of a single cycle length of the original AT. This is best explained by a continuation of AT that was "present" simultaneously with the pretransition tachycardia, being "entrained" (for a reentrant tachycardia) or "overdriven" for an automatic focal tachycardia. The presence of multiple tachycardia mechanisms active simultaneously would be consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Our analysis of approximately 150 cases in our database revealed that this phenomenon occurs in approximately one-third of the cases. Additionally, our review of the existing literature yielded consistent findings (Arantes et al, 2011;Takigawa et al, 2019;Kaiser, Rogers and Narayan, 2019). The observation that AT often transforms into a slower rhythm following ablation suggests the possibility of a secondary loop that plays a crucial role in ablation therapy.…”
Section: Revelation After Three Decades Of Ablation Therapy: Two Loop...supporting
confidence: 70%
“…Our analysis of approximately 150 cases in our database revealed that this phenomenon occurs in approximately one-third of the cases. Additionally, our review of the existing literature yielded consistent findings (Arantes et al, 2011;Takigawa et al, 2019;Kaiser, Rogers and Narayan, 2019). The observation that AT often transforms into a slower rhythm following ablation suggests the possibility of a secondary loop that plays a crucial role in ablation therapy.…”
Section: Revelation After Three Decades Of Ablation Therapy: Two Loop...supporting
confidence: 70%
“…In this issue of the JCE, Arantes 33 and coworkers advance still a new hypothesis derived from observations of the regular tachycardias occurring in the transition from AF to sinus rhythm, in the course of a “staged ablation” strategy progressing from PV isolation to CFE ablation in the coronary sinus and inferior LA, then to CFE ablation throughout the LA, then LA roof line ablation, and finally mitral isthmus ablation. In 29 of 90 patients they recorded 2 or more regular tachycardias, most of them LA MRT, before attaining sinus rhythm.…”
Section: Editorial Commentmentioning
confidence: 99%
“…Alternatively, they may reflect preexisting focal drivers uncovered after elimination of fibrillatory conduction. 22 There is evidence that presentation with these arrhythmias after PV isolation, and their successful ablation, results in better long-term outcomes than presentation with continuing or recurrent AF alone. 21,23 Why is persistent AF associated with potentially more non-PV drivers?…”
Section: Articles See P 287 295 and 442mentioning
confidence: 99%